REGIMES OF THERMAL STRENGTHENING AND CHARACTERISTICS OF ALLOY VT23 AT INCREASED TEMPERATURE - V. N. Fedulov (Литьë и металлургия, 2008)
The influence of the heating temperature at testing on mechanical characteristics and durability of the samples of plates of melt B23 is investigated.